Computing Stackelberg equilibrium for cancer treatment - Sam Ganzfried (Games, 2024)
Recent work by Kleshnina et al. has presented a Stackelberg evolutionary game model in which the Stackelberg equilibrium strategy for the leading player corresponds to the optimal cancer treatment. We present an approach that is able to quickly and accurately solve the model presented in that work.
Keywords: 330; evolutionary game; Stackelberg equilibrium; cancer treatment; optimization